Probing Deeper Mathematical Conceptual Understanding of PISA-like Uncertainty and Data - Wahyu Widada; Khathibul Umam Zaid Nugroho; Dewi Herawaty (Universitas PGRI Silampari, 2025)
This study explores the effectiveness of